2018
DOI: 10.3390/molecules23030535
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Stress Combination in Tomato Plants: New Insights in the Protective Role of Melatonin

Abstract: Abiotic stresses such as drought, heat or salinity are major causes of yield loss worldwide. Recent studies have revealed that the acclimation of plants to a combination of different environmental stresses is unique and therefore cannot be directly deduced from studying the response of plants to each of the different stresses applied individually. The efficient detoxification of reactive oxygen species (ROS) is thought to play a key role in enhancing the tolerance of plants to abiotic stresses. Here, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
213
2
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(236 citation statements)
references
References 65 publications
17
213
2
4
Order By: Relevance
“…Number of proteins of CBL-interacting kinase, serine threonine kinase and wall-associated receptor kinase and Mitogen-activated kinase family were highly expressed wheat, involved in metal ion binding and its transportation serine/threonine kinase signalling, protein phosphorylation and response to stresses [Jin et al, 2016; Mao et al,2009; Shi et al, 2018 Hou et al, 2005; Kanneganti et al, 2008; Kumar et al, 2018; Wimalasekera et al, 2018]. Glutathione peroxidase and peroxidase family proteins expression indicates higher response to oxidative stress, glutathione peroxidase activity, metal ions binding & transportation activity [Alzahrani et al 2018; Martinez et al, 2018]. Interestingly, number of transcripts of zinc finger transcription factors and helicase-like transcription factor were expressed in HZFWGs showed their function in various transcription factor activity, sequence-specific DNA and metal ion binding and stress response [Bouain et al, 2014; Zang et al, 2016; Sarwat et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…Number of proteins of CBL-interacting kinase, serine threonine kinase and wall-associated receptor kinase and Mitogen-activated kinase family were highly expressed wheat, involved in metal ion binding and its transportation serine/threonine kinase signalling, protein phosphorylation and response to stresses [Jin et al, 2016; Mao et al,2009; Shi et al, 2018 Hou et al, 2005; Kanneganti et al, 2008; Kumar et al, 2018; Wimalasekera et al, 2018]. Glutathione peroxidase and peroxidase family proteins expression indicates higher response to oxidative stress, glutathione peroxidase activity, metal ions binding & transportation activity [Alzahrani et al 2018; Martinez et al, 2018]. Interestingly, number of transcripts of zinc finger transcription factors and helicase-like transcription factor were expressed in HZFWGs showed their function in various transcription factor activity, sequence-specific DNA and metal ion binding and stress response [Bouain et al, 2014; Zang et al, 2016; Sarwat et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, N-acetyl-5-methoxytryptamin, is a wellknown hormone that played roles in plant response to abiotic stress [13,14]. Endogenous melatonin could be triggered by both moderate drought (withdrawing water) and cold (2 ± 0.5°C) conditions for 48 h, which was involved in drought priming and cold stress response in barley [13].…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous melatonin could be triggered by both moderate drought (withdrawing water) and cold (2 ± 0.5°C) conditions for 48 h, which was involved in drought priming and cold stress response in barley [13]. Martinez et al (2018) indicated that melatonin regulated genes and enzymes that were related to oxidative stress and ROS detoxification to improve tomato tolerance at combined salinity and heat [14]. In this study, significantly increased melatonin concentration was regarded as a responsive signal in tomato to the applied stresses, since the important roles of melatonin in plants at abiotic stress [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a single stress condition vs its control), there is a knowledge gap in the identification of QTLs involved in responses to combined stress. This aspect is of capital importance as it was shown that stress combination in tomato (biotic and/or abiotic) does not always have an additive effect regarding physiological, morphological, or biochemical responses compared with single stress (Rivero et al ., ; Bai et al ., ; Martinez et al ., ).…”
Section: Discovery Of Genetic Variations Underlying Major Traits In Tmentioning
confidence: 97%